Irritable Bowel Syndrome - current state of knowledge - Opala, Dominika; Staszczyk, Izabela; Szczotka, Dominika; Osuch, Dobromiła; Drabik, Aleksandra; Szemplińska, Antonina; Błachnio, Klaudia; Anderska, Agnieszka (Quality in Sport, 2024)
Introduction and objective: Irritable bowel syndrome (IBS) is a common gastroenterological disorder affecting 9% to 23% of the population worldwide. The disease causes recurrent abdominal pain and abnormal bowel movements without visible anatomical or biochemical changes and diagnosis is often difficult. The purpose of this paper is to analyze the current knowledge of the pathophysiology, risk factors, diagnosis and treatment of IBS. Review methods: The literature available in the PubMed database was reviewed using the following key words: "irritable bowel syndrome," "constipation," "diarrhea", "abdominal pain", "diagnostics", "treatment". 49 articles were included in the review and 80% were from 2016-2024. Current state of knowledge: The pathophysiology of IBS is not fully understood, but it is recognized that the disease is a disorder of the gut-brain axis. It can lead to abnormal secretion of serotonin and dopamine, which affects symptoms. The diagnosis of IBS is based on the Rome IV Criteria, defining the characteristics and severity of symptoms. Summary: IBS is a disorder that significantly affects quality of life. Diagnosis is based on the exclusion of organic diseases and meeting certain criteria. Treatment includes both dietary modification and pharmacotherapy aimed at relieving symptoms. Despite advances in research, the pathophysiology of IBS is still not fully understood, making it difficult to develop effective treatments.